COUNSELING OF DEATH ROUND CONVICTIONISTS IN CORRECTIONAL INSTITUTIONS IS LINKED TO LAW NUMBER 1 OF 2023 CONCERNING THE NATIONAL CRIMINAL CODE - Manase Putra; Yasmirah Mandasari Saragih; T. Riza Zarzani (International Journal of Synergy in Law, Criminal, and Justice, 2025)
This study aims to analyze the implementation of rehabilitation for death row inmates at Medan Class I Penitentiary (Tanjung Gusta) within the framework of Law Number 1 of 2023 concerning the National Criminal Code. Using a mixed-methods approach, this study explores the legal dynamics, structural constraints, and potential reforms that accompany the implementation of Article 100 of the Criminal Code, which introduces the conditional death penalty with a ten-year probationary period. The results show that the implementation of rehabilitation for death row inmates is still hampered by the absence of technical regulations, limited human resources, inadequate infrastructure, and the absence of a standardized evaluation mechanism. In this context, Tanjung Gusta Prison has not been able to optimally carry out its correctional function as required by a legal system that prioritizes corrective justice and humanity. Therefore, systemic policy intervention is needed so that rehabilitation for death row inmates does not become a merely symbolic procedure, but rather becomes a real instrument in determining changes in criminal status objectively and accountably.